Hybrid Magnetic-DNA Directed Immobilisation Approach for Efficient Protein Capture and Detection on Microfluidic Platforms - Elaheh Esmaeili (Nature Portfolio, 2017)
Abstract In this study, a hybrid magnetic-DNA directed immobilisation approach is presented to enhance protein capture and detection on a microfluidic platform. DNA-modified magnetic nanoparticles are added in a solution to capture fluorescently labelled immunocomplexes to be detected optically. A magnetic set-up composed of cubic permanent magnets and a microchannel was designed and implemented based on finite element analysis results to efficiently concentrate the nanoparticles only over a defined area of the microchannel as the sensing zone. This in turn, led to the fluorescence emission localisation and the searching area reduction. Also, compared to processes in which the immunocomplex is formed directly on the surface, the proposed approach provides a lower steric hindrance, higher mass transfer, lower equilibrium time, and more surface concentration of the captured targets leading to a faster and more sensitive detection. As a proof-of-concept, the set-up is capable of detecting prostate-specific membrane antigen with concentrations down to 0.7 nM. Our findings suggest that the approach holds a great promise for applications in clinical assays and disease diagnosis.